Reverse engineering of brake calliper design via integration of topology optimisation and lattice structure for additive manufacturing - Othman, Sheik Ahmad Taufiq; Azman, Abdul Hadi; Wahid, Zaliha; Azman, Muhammad Amin (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2024)
The emergence of additive manufacturing has enabled design improvements for automotive industry components, such as reducing weight and enhancing performance. However, the application of lightweight designs for automotive components is yet to be fully explored. Previous research have explored the different types of lattice structures and topology optimized parts, but have yet to explore its application in a brake calliper. This paper focuses on the design improvement of brake calliper for the automotive industry. The methodology consists of reverse engineering of an actual Volkswagen Golf Mk6 brake calliper and redesigning using topology optimisation and lattice structures. The new brake calliper design is then compared to the existing model in terms of weight reduction. The results show that through topology optimisation, it is possible to achieve weight reduction of brake calliper, while maintaining the part requirements. In conclusion, brake calliper designs can be improved using topology optimisation and lattice structures to achieve weight reduction. This research contributes to sustainability and reduces fuel consumption of cars through the decrease in part weight of automotive components, which is important in this era to comply with the environmental regulations and sustainability, in accordance with the UNESCO Sustainable Development Goals.